Differential Impact of Multiple Sclerosis on Cortical and Deep Gray Matter Structures in African Americans and Caucasian Americans. Issue 3 (16th September 2016) - Al‐Kawaz, Mais; Monohan, Elizabeth; Morris, Eric; Perumal, Jai S.; Nealon, Nancy; Vartanian, Timothy; Gauthier, Susan A.
ABSTRACT: BACKGROUND: African Americans with multiple sclerosis (AAwMS) have different disease phenotypes when compared to Caucasians Americans with MS (CAwMS). The pathologic basis of this difference in disease presentation is unknown. METHODS: Fifty‐Four AAwMS and 54 CAwMS were appropriately matched for age, gender, treatment duration, and disease duration. FreeSurfer was used to segment brain white matter and gray matter from T1 images and compute thalamic volume. Regional cortical thickness was calculated using QDEC. RESULTS: The 2 matched cohorts differed in disability, with AAwMS demonstrating significantly higher EDSS scores (2.3±2.2 vs. 1.3±1.5, P < .009), yet the 2 populations had similar T2 hyperintense lesion volumes ( P = .35). AAwMS had a significantly lower total global cortical thickness when compared to CAwMS ( P = .03). Controlling for EDSS, AAwMS showed multiple cortical regions to be significantly thinner than CAwMS; these included areas within the temporal, parietal and occipital lobes, as well as the precentral and postcentral gyrus. Middletemporal cortex was most affected in AAwMS in the left hemisphere ( P = .009), while the superiortemporal cortex was most affected in the right hemisphere ( P = .0001). In contrast, thalamic volume was significantly reduced in CAwMS when compared to AAwMS ( P = .01). In both groups, worse disability was associated with lower total thalamic volume percentage. CONCLUSION: AAwMS and CAwMS patients differ with regard to global and regional cortical thickness and thalamic volume. This diverging pattern of gray matter volumetrics among otherwise matched patients suggests that racial‐specific disease differences may exist.